Proceedings of the 2012 International Conference on Quantitative InfraRed Thermography 2012
DOI: 10.21611/qirt.2012.175
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the determination of the coefficient of thermal expansion of solid materials

Abstract: A new experimental method (IIC, Infrared Image Correlation) for quick assessment of the coefficients of thermal expansion of solid materials is presented. The proposed method is based on performing a digital image correlation between thermal images acquired at different temperatures by means of an infrared camera. It allows the coefficient of thermal expansion of both isotropic and anisotropic bulk materials to be determined by measuring simultaneously the fractional increase in length and the actual thermal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…By comparing the mean CTE values computed along the x and y directions, it can be concluded that brass exhibits, as expected, nearly isotropic thermal behaviour, since the small difference observed between the two values falls well within the measurement uncertainty (see section 4). Similar results were obtained by the authors testing Al alloy samples between 30 • C and 60 • C [16].…”
Section: Resultssupporting
confidence: 89%
“…By comparing the mean CTE values computed along the x and y directions, it can be concluded that brass exhibits, as expected, nearly isotropic thermal behaviour, since the small difference observed between the two values falls well within the measurement uncertainty (see section 4). Similar results were obtained by the authors testing Al alloy samples between 30 • C and 60 • C [16].…”
Section: Resultssupporting
confidence: 89%
“…The mechanical properties of the carbon fiber reinforced polymer structures (CFRP) significantly depend on the orientation of the fibers, the number of layers, layup technology and other factors.The unique feature of CFRP is the anisotropy of thermal expansion determined by the laying pattern of reinforcing fibers, namely the CTE is minimal along the fiber and maximum in the direction perpendicular to the fiber [25]. The increase in the number of reinforcing layers and the optimization of their reinforcement scheme make it possible to minimize thermal deformations of the construction.…”
Section: Problem Definitionmentioning
confidence: 99%
“…Esto se debe, en gran medida a su importancia en todas estas áreas del conocimiento, pero también en que es una experiencia relativamente fácil de llevar a cabo. Así podemos encontrar una amplia gama de trabajos dedicados a la demostración de la ley de dilatación térmica lineal desde los métodos más elementales y algunos demostrativos como ser el de la pelota y el aro o utilizando dos reglas plásticas idénticas pero sumergiendo una en nitrógeno líquido [1-3] hasta los más elaborados y precisos de superposición de imágenes infrarrojas, interferometría o simplemente usando un láser para amplificar la dilatación producida [4][5][6][7][8]. Dos review [9 y 10], resumen adecuadamente el estado del arte en los métodos y tecnología disponibles actualmente.…”
Section: Introductionunclassified